A study on The Low-Temperature Preservation of Paddy-straw Mushroom (Volvariella volvaceae) - Dhiah Nuraini; Suhardi Hardjo (Warta Industri Hasil Pertanian, 1986)
A study on the low-temperature preservation of paddy-straw mushroom (Volvariella volvaceace) has been carried out. Stages of treatments include trimming, washing, blanching (0, 2, 4 and 6 min), cooling (cool water spraying for 30 min), packaging (without packaging, packed in polyethylene and vacuum packed films), and storage at cool temperature. Observation were done on moisture content. PH, Total acid, suluble solid, activity of catalase and peroxidase, and organoleptic  test. The Results showed that paddy-straw mushroom can be preserved for two weeks at 7 degree-9 degree celcius in vacuum packaging (4-6 min blanching).